113k views
4 votes
Simplify the expression 3+2(2p+4t)+6+5p

User Ntoskrnl
by
5.2k points

2 Answers

5 votes
Start from the top and keep on going
User Ben Dauphinee
by
5.8k points
5 votes
Simplify the following:
3 + 2 (2 p + 4 t) + 6 + 5 p
Grouping like terms, 3 + 2 (2 p + 4 t) + 6 + 5 p = 2 (2 p + 4 t) + 5 p + (3 + 6):
2 (2 p + 4 t) + 5 p + (3 + 6)
3 + 6 = 9:
2 (2 p + 4 t) + 5 p + 9
2 (2 p + 4 t) = 4 p + 8 t:
4 p + 8 t + 5 p + 9
Grouping like terms, 4 p + 8 t + 5 p + 9 = 8 t + (4 p + 5 p) + 9:
8 t + (4 p + 5 p) + 9
4 p + 5 p = 9 p:
Answer: 8 t + 9 p + 9
User Adam Salma
by
6.5k points